Phase 1 study of AYP-101 (soybean phosphatidylcholine): safety, pharmacokinetics, and lipid profile effects for reducing submental fat - Hyun Joon Lee; Xu Jiang; A. M. Abd El-Aty; Ji Hoon Jeong; Jae-Yong Chung (Lipids in Health and Disease)
Abstract Background Excessive submental fat under the chin is a known aesthetic concern because of its negative impact on facial appearance and psychological well-being. AYP-101 is a newly developed injectable agent containing 93% soybean phosphatidylcholine (SPC) designed to reduce submental fat. We conducted a phase 1 study to evaluate the safety, pharmacokinetic (PK), and lipid profile effects of AYP-101. Methods This study was a randomized, double-blind, placebo-controlled, single-dose, two-cohort trial. Participants were randomized into groups receiving 250 mg of AYP-101, 500 mg of AYP-101, or placebo at a 9:9:8 ratio across both cohorts. Safety was assessed through standard clinical evaluations. Blood samples were collected up to 144 h postdose in cohort 1 and up to 48 h postdose in cohort 2. The PK parameters were calculated via noncompartmental analysis. Results All 26 randomized subjects completed the study. A total of 72 solicited adverse drug reactions (ADRs) were reported by 24 subjects, all of which were mild. The most common ADRs were injection site pain and bruising. There were 29 ADR cases in the 250 mg group; 26 cases in the 500 mg group; and 18 cases in the placebo group, indicating that there were no clinically significant differences in the safety profiles between the groups. All the dose groups presented similar PK profiles, with Cmax values of 12.86, 13.44, and 13.61 µg/L and AUC0−24 h values of 278.06, 274.79, and 267.63 µg*h/L, respectively. No clinically significant differences in PK or lipid profiles were observed between the postdose group and the baseline group for any of the dose groups. Conclusions AYP-101 appears to be a safe candidate for treating submental fat, with localized reactions and no systemic exposure at single subcutaneous doses of up to 500 mg. Trial registration ClinicalTrials.gov NCT05476094.